Straight from the horse`s mouth: understanding professional event riders` mental preparation for maximising self-confidence prior to competition using thematic analysis - McGinn, S.; Alcock, D.; Cameron, L. J. (Comparative Exercise Physiology, 2018)
High self-confidence or sport-confidence has been defined as a key psychological characteristic required by elite athletes, promoting optimal performance and helping manage competitive anxiety. Investigations have demonstrated that a mix of psychological interventions such as self-talk, goal setting, imagery, pre-performance routines and relaxation techniques are used by elite athletes as coping strategies. To date, most of this research has been carried out on collegiate athletes across a variety of sports but with limited research attention on equestrian sports. This study, using semi-structured interviews, explored five professional event riders` experiences of psychological interventions used leading up to and during elite level international competition. Thematic analysis identified two meta-themes; Planning and Preparation, Arousal and Distraction Management. The riders outlined the importance of goal-setting, managing time and pre-performance routines as part of planning and preparation. They discussed the use of interventions such as self-talk and imagery in managing arousal levels with support teams playing a key role in distraction management. The findings from this study support previous research, suggesting that these riders have similar approaches to other non-equestrian athletes in their use of a combination of coping strategies to manage competition anxiety and build self-confidence.